Quantitative domain engineering for realizing d36 piezoelectric coefficient in tetragonal ceramics. (15th April 2020) - Wu, Jingen; Hu, Zhongqiang; Gao, Xiangyu; Chu, Zhaoqiang; Dong, Guohua; Wang, Zhiguang; Peng, Bin; Peng, Ren-Ci; Zhou, Ziyao; Dong, Shuxiang; Liu, Ming
Abstract: Piezoelectric devices based on d 36 mode are remarkably stable that depolarization rarely occurs in d 36 face shear mode, because d 36 mode is completely different from d 15 thickness shear mode, where the applied electric field is perpendicular to poling direction and depolarization is ineluctable due to 90° dipole rotation. However, piezoelectric ceramics conventionally possess three piezoelectric coefficients (i.e., d 33, d 31, and d 15 ), while d 36 only exists in single crystals of specific point groups and cut directions. In this work, we propose a method to realize d 36 piezoelectric coefficient in tetragonal piezoelectric ceramics by mechanical and electric domain engineering. This method is successfully applied in bismuth scandium-lead titanate (abbreviated as BS-PT) high-temperature piezoelectric ceramics with a resultant d 36 up to 160 pC/N, which broadens the application of BS-PT ceramics, such as face shear actuator, energy harvester, transducer, etc. We find that domain engineering by transversal electric poling is preferred compared with the transversal mechanical poling, due to the simpler process, higher reliability, and higher resultant d 36 piezoelectric coefficient. By combining the Diffraction-Plane-Transformation (DPT) model with the domain engineering via transversal electric poling, we demonstrate a quantitative domain engineering method for the first time, which could be used for optimizing the piezoelectric properties by precise design of the domain structures in piezoelectric materials. Graphical abstract: d 36 piezoelectric coefficient in tetragonal piezoelectric ceramics is successfully realized by a quantitative domain engineering, demonstrating a novel method for optimizing the piezoelectric properties via precise design of the domain structures in piezoelectric materials. Image, graphical abstract